The Jewish background of Indian people A historical, archaeological, anthropological and etymological study of the lost tribes of Israel - Braham Benhur (Jeevanist books, 2011)
One thing that becomes obvious from a careful examination of religious texts and modern scientific evidence is the fact that the huma race had its origin in the family of Noah, who settled down after the Great Flood in Eastern Turkey, in the basins of the Euphrates, the Tigris and the Aras rivers originating in the foothills of the Ararat Mountain. The history of the human race after the flood began at once point, and from one family. The family has given rise to teachers, leaders, priests, artists, scientists, workers and soldiers. Knowing the history of the family enables us to recognize not only the society but also ourselves. This in turn helps us to trace our roots and discover the Great Human Family to which we all belong. It enables us to identify our brethern. Every human being on earth is our cousin whether first, second, third or the thousandth...!